A scoping review of the role of spirituality in dealing with loss and grief among cancer patients - Ismail, Shehenaz; Mohamad, Mardiana; Abdul Khaiyom, Jamilah Hanum; Dzulkifli, Mariam Adawiah (Morse Florse, 2023)
Cancer is one of the most commonly occurring terminal illnesses across the globe affecting millions of people and their loved ones. When someone experiences such a terminal illness, the experience is negatively perceived creating a loss and grief reaction which affects the person's psychospiritual aspects of life. Many patients and caregivers adopt various coping strategies including spiritual concepts. Hence this study aims to review existing literature to understand the role of spirituality in dealing with the loss and grief experiences of cancer patients. A search on Ebsco Discovery Service was conducted for peer reviewed, English, full-text academic articles between January 2017 to December 2020. A total of 602 articles were found, out of which 13 articles were accepted after screening for eligibility. All these 13 articles are reported in this paper. From the 13 articles major 4 themes were extracted which are, belief in God, having faith and hope, Spiritual acts and comfort through a higher power.